Pengaruh Bibliotherapy Terhadap Perkembangan Karakter Disiplin Pada Siswa Sekolah Dasar - titi setiawati; Nia Royani (Universitas Negeri Makassar, 2018)
Strengthening character education as one of efforts improving the future generation should be done continually. One of the character values that should be a concern is discipline character. This research aims at to analyze bibliotherapy effect on the students’ discipline character improvement. The research method used was experiment with one group pretest-postest design. The research subject was students in IV grade SDN 1 Sukaraja, Sumedang. The instruments used in this study were questionnaires and observation sheets to measure the discipline character of students before and after bibliotherapy treatment. Hypothesis test results used Non Parametric Wilcoxon signed ranks statistical test showed that there was a significant change in the discipline character of students before and after being given bibliotherapy treatment. The statistical tests that was conducted obtaining sig = 0.000 the value is smaller than 0.05 so H0 is rejected. It is meant that there is an effect of bibliotherapy treatment on the students’ discipline character.